2008
DOI: 10.1177/147323000803600511
|View full text |Cite
|
Sign up to set email alerts
|

The Effect on the Recovery Profile of a Change from Enflurane to Desflurane during the Latter Part of Anaesthesia

Abstract: This study compared emergence and recovery characteristics after either enflurane anaesthesia or crossover from enflurane to desflurane anaesthesia. At an estimated 1 h prior to the end of operation, enflurane was either reduced (group E, n = 23) or replaced with desflurane (group X, n = 23). At the end of the operation, emergence and recovery characteristics of the two groups were compared. The crossover technique accelerated recovery compared with enflurane anaesthesia. The time taken for the eyes to open in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Several studies have investigated the effects of changing from isoflurane to desflurane during the latter part of anesthesia, [19][20][21] and Kang et al have reported that changing from enflurane to desflurane effectively improved recovery from general anesthesia. 22 Nevertheless, few studies have reported the advantages of changing from sevoflurane to desflurane. In the present study, none of the patients experienced severe adverse events during volatile induction, and changing from Data are expressed as means (SD) or difference (95% CI).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the effects of changing from isoflurane to desflurane during the latter part of anesthesia, [19][20][21] and Kang et al have reported that changing from enflurane to desflurane effectively improved recovery from general anesthesia. 22 Nevertheless, few studies have reported the advantages of changing from sevoflurane to desflurane. In the present study, none of the patients experienced severe adverse events during volatile induction, and changing from Data are expressed as means (SD) or difference (95% CI).…”
Section: Discussionmentioning
confidence: 99%